Effect of Different Physiotherapy Programs on Pain and Functional State of the Torso in Individuals with Chronic Non-Specific Lower Back Pain - Erika Prišmontaitė; Saulė Sipavičienė (Lithuanian Sports University, 2019)
Research background. In the modern society, lower back pain is the most widespread health disorder with negative economic consequences for healthcare costs and labour productivity. According to the epidemiological research, lower back pain is ranked 6th out of 291 diseases and conditions, that cause the highest rate worldwide of incapacity to work. The aim of the research was to establish the eﬀect of diﬀerent physoiotherapy methods on pain, torso functional of people with chronic non-specifc lower back pain. Methods. Forty patients were included in the study. Subjects were divided into control and three experimental groups: back-stabilization exercises group; physiotherapy in water group; Nordic walking group. We measured intensity of lower back pain, functional state of the torso, mobility of lumbar spine, active movements amplitudes and the static endurance of the torso. Results. It was found that all the analysed parameters statistically significantly (p < 0.05) improved in all examined groups. While assessing the results of the investigated groups interdependently, it was determined that the parameters such as: the intensity of the pain, the functional state and the mobility of the torso, statistically signifcantly (p < 0.05) improved more eﬀectively in the physiotherapy in water and back-stabilization exercise groups in comparison with the Nordic walking group. Conclusions. Physiotherapy procedures in water and back-stabilization exercises decreased the intensity of the pain and functional disability, improved the lumbar spine mobility and active movements amplitudes, more efciently than the programme of Nordic walking, for people with chronic non-specifc lower back pain. However, all three types of exercises equally increased the static endurance of the torso. Keywords: chronic non-specifc lower back pain, spinal stabilization exercises, physiotherapy in water, Nordic walking.